Analysis of Errors in the Use of Punctuation Marks and Writing Words on Signboards in the Kayuagung Area - Wardarita, Ratu; Sartika, Nining; Mispita, Eva (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Language is an arbitrary system of sound symbols used by members of a society to cooperate, interact, and identify themselves. The problem in this study is the misuse of punctuation marks and errors in writing words on signboards in the Kayuagung area. This study aims to describe the errors in the use of punctuation marks and word writing errors on signboards in the Kayuagung area in particular. Thus it can provide information, how to use punctuation and write words correctly in accordance with Enhanced Spelling (EYD) so that these mistakes are expected not to be repeated again. The method used in this study is qualitative descriptive method. The data collection technique used in this study is to use observation techniques, documentation, see notes. The object used is a signboard or signpost located in the Kayuagung area. The result of this study is that there are still many errors found in the use of punctuation marks on signage for one's title. Errors in writing words such as errors in the use of standard words, and errors in combining words.